Ответ:
Пошаговое объяснение:
y(-2) = 4 - 2(-2) - 3 = 4+4-3=5
y(-1) = 1 - 2(-1) - 3 = 1+2-3=0
y(0) = 0-2*0-3 = -3
y(1) = 1 - 2 - 3 = -4
y(2) = 4 - 4 - 3 = -3
y(1/2) = 1/4 - 1 - 3 = -3(3/4)
y(1/3) = 1/9 - 2/3 - 3 = 1/9 - 6/9 - 3 = -3(5/9)
y(1/4) = 1/16 - 1/2 - 3 = -3(7/16)
y(1/5) = 1/25 - 2/5 - 3 = -3(9/25)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
y(-2) = 4 - 2(-2) - 3 = 4+4-3=5
y(-1) = 1 - 2(-1) - 3 = 1+2-3=0
y(0) = 0-2*0-3 = -3
y(1) = 1 - 2 - 3 = -4
y(2) = 4 - 4 - 3 = -3
y(1/2) = 1/4 - 1 - 3 = -3(3/4)
y(1/3) = 1/9 - 2/3 - 3 = 1/9 - 6/9 - 3 = -3(5/9)
y(1/4) = 1/16 - 1/2 - 3 = -3(7/16)
y(1/5) = 1/25 - 2/5 - 3 = -3(9/25)